The Influence of The Value of Oil and Gas Exports and Imports on The Country's Foreign Exchange from 2010-2017 - Purnama, Intan; Putra, Rizaldi; Syahputra, Hidayat; Yani, Fitri; Eddy, Pujiono (First Ciera Publisher, 2024)
International trade requires a very important source of financing, namely foreign exchange reserves. Foreign exchange reserves are the net position of foreign assets of the government and foreign exchange banks, which must be maintained for international transaction purposes. This research aims to determine the effect of oil and gas exports, namely crude oil, oil and gas products on foreign exchange reserves in Indonesia. The type of data used in this research is secondary data obtained from the Central Statistics Agency website, data taken from BPS is the value of oil and gas exports and imports for 1996-2017 and the position of foreign exchange reserves for 2005-2018. The method used in this research is the Simple Linear Regression Method which is used to see the form of relationship between variables through an equation. From the research results above, it can be concluded that oil and gas exports and imports in 2010-2017 did not have a significant effect on the country's foreign exchange reserves. This shows the lack of contribution of exports and imports of crude oil, oil and gas products in influencing the country's foreign exchange reserves.